Gardening as a responsible leisure activity: The geography of Central European food self-provisioning - Daněk , Petr; Jehlička, Petr (ERDKUNDE, 2024)
Recent research on food self-provisioning (FSP) has pointed to its material similarity with the practices of alternative food networks (AFNs) – a subject of enormous scholarly interest in the last two decades. Most of the limited research on FSP has so far focused on comparing gardeners with the non-gardening population in a single country and overlooked geographical differences in FSP practices. The objective of this article is to assess the differences in FSP in two Central European countries (Austria and Czechia) and between urban, suburban and rural areas. More specifically, we have analysed robust survey data on 1,284 households practising gardening with the objective of comparing FSP practices in different geographical settings in terms of time spent in the garden, motivations for growing food, the volume of vegetable production, the extent of mutual help and food sharing and fertiliser and pesticide use. The results reveal similarities rather than differences between geographical categories, despite a significant disparity in living standards between the two countries. Associating FSP with the quality of produce and a leisure activity rather than poverty or obligation, as well as proving its comparable relevance in both rural and urban areas and across international boundaries, contributes to bridging the gap between research on AFNs and FSP. It also demonstrates that food alternatives have significantly greater material significance in terms of volume of production and the number of participants than previously realised.